Modified 7xxx series aluminum alloy powder, additive manufacturing aluminum alloy and preparation method of modified 7xxx series aluminum alloy powder

By modifying the 7xxx aluminum alloy powder and optimizing the L-PBF process parameters, the problem of aluminum alloy prone to cracks in additive manufacturing is solved, significantly improving its mechanical properties and broadening its application range.

CN119753456APending Publication Date: 2025-04-04KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510038608.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing 7xxx series aluminum alloys are prone to cracks in the L-PBF process, which seriously affects its mechanical properties and limits its application range.

Method used

Modified 7xxx aluminum alloy powder is used, and its composition includes Cu, Mg, Zn, Si, Ag, Cr, Mn, Ti and other elements. It is manufactured after drying and vacuum treatment, and process parameters such as energy density, laser power and scanning speed are adjusted to reduce thermal expansion and improve melt flowability.

Benefits of technology

It effectively reduces the crack phenomenon of aluminum alloy in the additive manufacturing process, refines the alloy structure, improves the bending strength, hardness and other properties, and significantly improves the comprehensive mechanical properties, broadens its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753456A_ABST
    Figure CN119753456A_ABST
Patent Text Reader

Abstract

The invention discloses modified 7xxx series aluminum alloy powder, an additive manufacturing modified 7xxx series aluminum alloy and a preparation method of the modified 7xxx series aluminum alloy, and belongs to the technical field of aluminum alloy additive manufacturing, and the aluminum alloy powder is prepared from the following components in percentage by mass: 1.2 to 2.0 percent of Cu, 2.1 to 2.9 percent of Mg, 5.1 to 6.5 percent of Zn, 0.01 to 2.6 percent of Si, 0.01 to 0.8 percent of Ag, 0.04 to 0.28 percent of Cr, 0.04 to 0.3 percent of Mn, 0.1 to 0.2 percent of Ti and the balance of Al. The modified 7xxx series aluminum alloy powder has the advantages that the modified 7xxx series aluminum alloy powder can be suitable for a laser powder bed melting (L-PBF) additive manufacturing process, the phenomenon that cracks are generated in the additive manufacturing process of 7xxx series aluminum alloy can be effectively improved, a prepared molded part is basically free of cracks and few in pores, the bending strength is obviously improved, and the service life of the molded part is prolonged. The comprehensive mechanical property is obviously improved, and the application range is further widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy additive manufacturing, and in particular to a modified 7xxx series aluminum alloy powder, an additively manufactured aluminum alloy and a preparation method thereof. Background Art

[0002] Powder bed fusion (L-PBF) is considered to be the most widely used and most extensively researched metal additive manufacturing process. It can use loose powder and laser as a heat source to manufacture high-precision metal parts and lightweight components through the discrete stacking principle, and reduce material waste. It is widely used in many fields such as aerospace, medical, nuclear power, molds and automobiles. Aluminum alloys have the characteristics of low density, high specific strength, excellent electrical and thermal conductivity, non-toxicity and easy recycling. They are widely used in the fields of shipbuilding, chemical industry, aerospace and metal packaging. The technical added value of additively manufactured aluminum alloy parts is high and has a wide application market.

[0003] At present, most high-strength aluminum alloys used in the L-PBF process use materials with standard grades, such as traditional 7xxx series aluminum alloys. However, existing 7xxx series aluminum alloys have high thermal crack sensitivity. In L-PBF processing, 7xxx aluminum alloys are very prone to cracks, which seriously affects their mechanical properties and greatly limits their application range. Therefore, the preparation of crack-free aluminum alloys with excellent mechanical properties suitable for the L-PBF process is an important technical problem that needs to be solved urgently. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a modified 7xxx series aluminum alloy powder suitable for L-PBF process, which is crack-free and has excellent mechanical properties, an additively manufactured aluminum alloy and a preparation method thereof.

[0005] In order to solve the above technical problems, the present invention provides a modified 7xxx series aluminum alloy powder, which includes the following components by mass percentage: Cu: 1.2~2.0wt.%, Mg: 2.1~2.9wt.%, Zn: 5.1~6.5wt.%, Si: 0.01~2.6wt.%, Ag: 0.01~0.8wt.%, Cr: 0.04~0.28wt.%, Mn: 0.04~0.3wt.%, Ti: 0.1~0.2wt.%, and the balance is Al.

[0006] The present invention also provides an additively manufactured aluminum alloy, the raw materials of which include the above-mentioned modified 7xxx series aluminum alloy powder.

[0007] The present invention also provides a method for preparing an aluminum alloy by additive manufacturing, comprising the following steps: S1, geometric model pre-processing; S2, placing the modified 7xxx series aluminum alloy powder in a vacuum drying oven for drying, and filling after drying; S3, vacuuming or washing, and preheating the substrate, and then performing additive manufacturing after preparation; S4. Wait for all layers to melt and solidify, and take out the sample after the substrate cools down.

[0008] Furthermore, the energy density during additive manufacturing in step S3 is 118 J / mm 3 ~160J / mm 3 .

[0009] Furthermore, in the step S3, the laser power during additive manufacturing is 300W to 360W, and the laser scanning speed is 300mm / s to 1050mm / s.

[0010] Furthermore, in the step S3, the interlayer spacing during additive manufacturing is 0.048 mm to 0.105 mm, and the layer thickness is 0.06 mm.

[0011] Furthermore, in step S2, the drying time is 4 hours to 8 hours, the vacuum degree is less than -80 KPa, and the drying temperature is 80° C. to 130° C.

[0012] Beneficial effects of the present invention: Compared with the traditional 7xxx series high-strength aluminum alloy, the modified 7xxx series aluminum alloy powder provided by the present invention has added Si and Ag elements, which can reduce the melting point temperature and solidification temperature range of the alloy, improve the melt fluidity, and reduce the thermal expansion in the part manufacturing process, so that it can be better applied to the L-PBF additive manufacturing process. The present invention can effectively improve the phenomenon of cracks in the 7xxx series high-strength aluminum alloy during the additive manufacturing process, and refine the alloy structure. The prepared sample is basically crack-free, with few pores, and the properties such as bending strength and hardness are significantly improved, and the comprehensive mechanical properties are significantly improved, further broadening its application range. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a micrograph of the sample prepared in Example 6; Figure 2 This is a micrograph of the sample prepared in Example 7; Figure 3 This is a micrograph of the sample prepared in Example 8; Figure 4 This is a micrograph of the sample prepared in Comparative Example 1; Figure 5 This is a micrograph of the sample prepared in Comparative Example 2; Figure 6 The EBSD image of Example 6 and the frequency distribution diagram of the grain area in the region; Figure 7 The EBSD image of Example 7 and the frequency distribution diagram of the grain area in the region; Figure 8 The EBSD image of Example 8 and the frequency distribution diagram of the grain area in the region; Fig. 9 It is the EBSD image of comparative example 1 and the statistical diagram of the frequency distribution of grain area in the region. DETAILED DESCRIPTION

[0014] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0015] Example 1 An aluminum alloy powder comprises the following components, measured by mass percentage: Cu: 1.4wt.%, Mg: 2.3wt.%, Zn: 6.5wt.%, Si: 2.6wt.%, Ag: 0.8wt.%, Cr: 0.05wt.%, Mn: 0.04wt.%, Ti: 0.1wt.%, and the balance is Al.

[0016] Example 2 An aluminum alloy powder comprises the following components, measured by mass percentage: Cu: 1.4wt.%, Mg: 2.3wt.%, Zn: 6.5wt.%, Si: 2.6wt.%, Ag: 0.01wt.%, Cr: 0.28wt.%, Mn: 0.3wt.%, Ti: 0.2wt.%, and the balance is Al.

[0017] Example 3 An aluminum alloy powder comprises the following components, measured by mass percentage: Cu: 2.0wt.%, Mg: 2.9wt.%, Zn: 5.1wt.%, Si: 0.01wt.%, Ag: 0.4wt.%, Cr: 0.05wt.%, Mn: 0.04wt.%, Ti: 0.1wt.%, and the balance is Al.

[0018] Example 4 An additively manufactured aluminum alloy, the raw material of which includes the aluminum alloy powder in Example 1.

[0019] Example 5 An additively manufactured aluminum alloy, the raw material of which includes the aluminum alloy powder in Example 2.

[0020] Example 6 A method for preparing an aluminum alloy by additive manufacturing comprises the following steps: S1. Geometric model pre-processing: The model is reasonably placed in space and supported by geometric model pre-processing and additive manufacturing process planning software. Finally, the processed model is sliced ​​and given additive manufacturing parameters: laser power is 300W, laser scanning speed is 300mm / s, layer spacing is 0.105mm, layer thickness is 0.06mm; energy density is 158J / mm 3 ; S2. Place the aluminum alloy powder of Example 1 in a vacuum drying oven and dry it for 5 hours at a drying temperature of 130° C. and a vacuum degree of less than -80 KPa; and fill the powder after drying. S3, washing and preheating the substrate, and then performing additive manufacturing after preparation; S4, wait for all layers to melt and solidify, and take out the additively manufactured aluminum alloy after the substrate cools down.

[0021] The prepared additively manufactured aluminum alloy sample was placed under a microscope for observation, and the morphology was observed as follows Figure 1 As shown, it can be seen that the sample surface has few pores and no cracks; the sample was subjected to a three-point bending test, and the average bending strength was tested to be 872MPa. The Vickers hardness was tested to be 124.65 HV0.1. The sample was also observed by scanning electron microscopy, and the EBSD image obtained and the frequency distribution statistics of the grain area in the region calculated based on the EBSD data are shown in Figure 6 shown.

[0022] Example 7 A method for preparing an aluminum alloy by additive manufacturing comprises the following steps: S1. Geometric model pre-processing: The model is reasonably placed in space and supported by geometric model pre-processing and additive manufacturing process planning software. Finally, the processed model is sliced ​​and given additive manufacturing parameters: laser power is 300W, laser scanning speed is 300mm / s, layer spacing is 0.105mm, layer thickness is 0.06mm; energy density is 158J / mm 3 ; S2, placing the aluminum alloy powder of Example 2 in a vacuum drying oven for drying for 8 hours, the drying temperature is 80° C., and the vacuum degree is less than -80 KPa; after the drying is completed, filling is performed; S3, washing and preheating the substrate, and then performing additive manufacturing after preparation; S4, wait for all layers to melt and solidify, and take out the additively manufactured aluminum alloy after the substrate cools down.

[0023] The prepared additively manufactured aluminum alloy sample was placed under a microscope for observation, and the morphology was observed as follows Figure 2As shown, it can be seen that there are no cracks on the surface of the sample, but the pores have increased. The sample was subjected to a three-point bending test, and the average bending strength was tested to be 703MPa. The Vickers hardness was tested to be 112.58 HV0.1. The sample was also observed by scanning electron microscopy, and the EBSD image obtained and the frequency distribution of grain area in the region calculated based on the EBSD data are shown in the figure below. Figure 7 shown.

[0024] Example 8 A method for preparing an aluminum alloy by additive manufacturing comprises the following steps: S1. Geometric model pre-processing: The model is reasonably placed in space and supported by geometric model pre-processing and additive manufacturing process planning software. Finally, the processed model is sliced ​​and given additive manufacturing parameters: laser power is 359W, laser scanning speed is 1050mm / s, layer spacing is 0.048mm, layer thickness is 0.06mm; energy density is 118J / mm 3 ; S1. Place the aluminum alloy powder of Example 1 in a vacuum drying oven and dry it for 4 hours at a drying temperature of 130° C. and a vacuum degree of less than -80 KPa. After drying, fill the powder; S2, washing and preheating the substrate, and then performing additive manufacturing after preparation; S3, wait for all layers to melt and solidify, and take out the additively manufactured aluminum alloy after the substrate cools down.

[0025] The prepared additively manufactured aluminum alloy sample was placed under a microscope for observation, and the morphology was observed as follows Figure 3 As shown, it can be seen that there are no cracks on the surface of the sample and few pores. The sample was subjected to a three-point bending test, and the average bending strength was tested to be 761MPa. After testing, its Vickers hardness was 113.143HV0.1. The sample was also observed by scanning electron microscopy, and the EBSD image obtained and the frequency distribution statistics of the grain area in the region calculated based on the EBSD data are shown in Figure 8 shown.

[0026] Comparative Example 1 The powder used is 7075 aluminum alloy powder commonly used in industry, and its composition is: Cu: 1.59wt.%, Mg: 2.52wt.%, Zn: 5.99wt.%, Cr: 0.05wt.%, Mn: 0.04wt.%, Ti: 0.1wt.%, and the balance is Al; Through geometric model pre-processing and additive manufacturing process planning software, the model is reasonably placed in space and supports are added. Finally, the processed model is sliced ​​and given additive manufacturing parameters. The 7075 aluminum alloy powder is placed in a vacuum drying oven and dried for 5 hours at a drying temperature of 130°C and a vacuum degree of less than -80KPa; the dried powder is loaded into the machine; Argon gas is introduced to remove the air in the molding chamber to the maximum extent and preheat the substrate; after the preparation is completed, additive manufacturing is carried out, the laser power is 359W, the laser scanning speed is 1050mm / s, the layer spacing is 0.048mm, the layer thickness is 0.06mm; the energy density is 118J / mm 3 ; Wait for all layers to melt and solidify, and then take out the sample after the substrate cools down.

[0027] The sample was placed under a microscope for observation and its morphology was observed. Figure 4 As shown in the figure, it can be seen that the sample has many surface cracks and pores. The sample was subjected to a three-point bending test, and the average bending strength was only 130MPa, which is completely unsuitable for any scenario. The Vickers hardness was tested to be 87.66HV0.1. The sample was also observed by scanning electron microscopy, and the EBSD image obtained and the frequency distribution of grain area in the region calculated based on the EBSD data are shown in the figure below. Fig. 9 shown.

[0028] Comparative Example 2 Compared with Example 6, the powders used are the same as those in Example 1, but the additive manufacturing process parameters are changed. Specifically, the laser power is 241W, the laser scanning speed is 2150mm / s, the layer spacing is 0.01mm, the layer thickness is 0.06mm, and the energy density is 187J / mm 3 ; After the additive manufacturing is completed, the sample is taken out and observed under a microscope. The morphology is as follows Figure 5 As shown, although the sample surface cracks are less than that of comparative example 1, there are many pores. The sample was subjected to a three-point bending test, and the average bending strength was only 135MPa, which is also unusable in any scenario. Due to too many defects, no hardness test was performed.

[0029] It can be seen that compared with Comparative Example 1, Example 8 has a different powder formula and the same additive manufacturing process parameters, but the bending strength of Example 8 is 761MPa and the Vickers hardness is 113.143HV0.1; the bending strength of Comparative Document 1 is only 130MPa and the Vickers hardness is 87.66HV0.1. It can be seen that compared with Comparative Example 1, the bending strength of Example 8 is increased by 5.85 times, and the Vickers hardness is increased by 1.29 times.

[0030] It can be seen intuitively from the EBSD image that the sample area of ​​comparative example 1 is 0-100µm 2The proportion of small grains between the two samples is only 61.2%. In Examples 6-8, the area of ​​the small grains is between 0 and 100 μm. 2 The proportion of small grains in the sample 1 is more than 80%; the area of ​​the sample 2 is larger than 1000µm 2 The proportion of grains in Examples 6, 7, and 8 is more than 1.5%, which is much higher than 0.205%, 0.39%, and 0.318% in Examples 6, 7, and 8, respectively. The addition of Si and Ag promotes nucleation and recrystallization, refines the grains, and increases the average grain area in Examples 6, 7, and 8 from 313.1 μm in Comparative Example 1 to 0.318 μm in Comparative Example 1. 2 Down to 78.946µm 2 、106.674µm 2 、96.25µm 2 .

[0031] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.

Claims

1. A modified 7xxx series aluminum alloy powder, characterized in that: Calculated by mass percentage, it includes the following components: Cu: 1.2~2.0wt.%, Mg: 2.1~2.9wt.%, Zn: 5.1~6.5wt.%, Si: 0.01~2.6wt.%, Ag: 0.01~0.8wt.%, Cr: 0.04~0.28wt.%, Mn: 0.04~0.3wt.%, Ti: 0.1~0.2wt.%, and the balance is Al.

2. An additively manufactured aluminum alloy, characterized in that: The raw material for additive manufacturing of aluminum alloy includes the modified 7xxx series aluminum alloy powder described in claim 1.

3. A method for preparing an aluminum alloy by additive manufacturing, characterized in that: The steps include: S1, geometric model pre-processing; S2. placing the modified 7xxx aluminum alloy powder according to claim 1 in a vacuum drying oven for drying, and filling the powder after drying; S3, vacuuming or washing, and preheating the substrate, and then performing additive manufacturing after preparation; S4, wait for all layers to melt and solidify, and take out the additively manufactured aluminum alloy after the substrate cools down.

4. The method for preparing aluminum alloy by additive manufacturing according to claim 3, characterized in that: The energy density during additive manufacturing in step S3 is 118 J / mm 3 ~160J / mm 3 .

5. The method for preparing aluminum alloy by additive manufacturing according to claim 3, characterized in that: In the step S3, the laser power during additive manufacturing is 300W to 360W, and the laser scanning speed is 300mm / s to 1050mm / s.

6. The method for preparing aluminum alloy by additive manufacturing according to claim 3, characterized in that: In the step S3, the interlayer spacing during additive manufacturing is 0.048 mm to 0.105 mm, and the layer thickness is 0.06 mm.

7. The method for preparing aluminum alloy by additive manufacturing according to claim 3, characterized in that: In step S2, the drying time is 4 hours to 8 hours, the vacuum degree is less than -80 KPa, and the drying temperature is 80° C. to 130° C.